Navigating Racial Identity: Denial, Repression, and Resilience in Novel Caucasia by Danzy Senna - Dani , Ammar; Iman, Diah Tyahaya (Program Studi Sastra Inggris, 2026)
This study examines Racial Identity, Denial, Repression and Resilience in Danzy Senna's Caucasia. This research identifies how the author depicts Birdie's racial identity development, defense mechanisms, and resilience in responding to social expectations. This study employs a descriptive qualitative method, applying Sigmund Freud's